Synthetic Applications of Sulfonium Salts - Kozhushkov, Sergei I.; Alcarazo, Manuel (European journal of inorganic chemistry, 2020)
This minireview aims to cover the developments over the past two decades in the chemistry of sulfonium salts. Specifically, insight is provided into the synthetic strategies available for the preparation of these compounds, the different reactivity patterns that are expected depending on their structural features or the reaction conditions applied, and the diversity of organic scaffolds that can thereby be synthesized. Additionally, the pros and cons derived from the use of sulfonium salts are presented and critically compared, when possible, in relation to reagents not based on sulfur but depicting similar reactivity. Quo vadis sulfonium? This minireview compiles the recent developments in the chemistry of sulfonium salts in terms of preparation, reactivity and synthetic utility. Additionally, the pros and cons derived from their use are critically evaluated, when possible, in relation to reagents not based on sulfur but depicting similar reactivity.